## Solve the following equations ) ((m-1))/2 – (( m-2))/3 = (( m-4 ))/7

Question

Solve the following equations ) ((m-1))/2 – (( m-2))/3 = (( m-4 ))/7

in progress
0

Mathematics
4 months
2021-08-01T10:46:48+00:00
2021-08-01T10:46:48+00:00 2 Answers
0 views
0
## Answers ( )

Answer:m – (m – 1)/2 = 1- (m – 2)/3

(2m – m + 1)/2 = (3 – m + 2)/3

(m + 1)/2 = ( 5 – m)/3

3(m + 1) = 2(5 – m)

3m + 3 = 10 – 2m

3m + 2m = 10 – 3

5m = 7

m = 7/5

Step-by-step explanation:plz mark as brainliest..

Answer:Step-by-step explanation: